"In search of a good life": Perspectives on village out-migration in a Tanzanian marine park. (August 2019) - Raycraft, Justin
Abstract: This paper draws from ethnographic fieldwork conducted between August–October 2014 and July–August 2015 in a rural village located inside of a Tanzanian marine park. Through narrative responses elicited during interviews with village residents, coupled with ethnographic vignettes from a key interlocutor in the village, the paper reveals people's diverse perspectives on village out-migration. In doing so, it interrogates the claim that the marine park has forced people to out-migrate. Some respondents explained that men generally engage in circular forms of labour-related mobility in the context of seasonal fishing activities and short-term business ventures. Others said that people choose to out-migrate due to everyday hardships, leaving "in search of a good life." These narrative responses are at once commentaries on the macro-level political and economic drivers of rural out-migration, and on respondent's micro-level aspirations for future socioeconomic autonomy. Thus, they are both expressions of structural constraint and individual agency. While very few interviewees believed that people were forced to migrate because of the marine park, most respondents contended that it had deepened pre-existing experiences of a "hard life, " and exacerbated lived experiences of vulnerability. However, migration has historically been woven into the sociocultural fabric of the community, and there are broader trends of rural population mobility in Tanzania, and fisher mobility in coastal areas, which long pre-date the establishment of the park. Furthermore, some respondents offered alternative narratives, noting that villagers may choose not to out-migrate, and that village in-migration may be increasing due to various pull factors. As such, the paper complicates the scholarly discourse on the relationship between marine protected areas and displacement of local communities. Highlights: I interrogate the claim that the marine park has forced villagers to out-migrate. Coastal villagers are vulnerable to 'multiple livelihood stressors'. Migration drivers are sociocultural, economic, psychological, political, and environmental. Patterns of migration are historically embedded. Migration from inside the MPA is a product of agency and structural constraint.